Determination the concentration of heavy metal (Cd, Cu, And Pb) in the wild shrimp and aquaculture shrimp along with health risk estimation on consumer / Mohd Nor Shukri Yahya - Yahya, Mohd Nor Shukri (2011)
Introduction: Heavy metal refers to metals and metal compounds that negatively affect people's health and is toxic or poisonous at low concentrations. West coast of Malaysia is interesting area for investigation of heavy metal trace since the area is likely receive impact of anthropogenic activity. Marine living like P. merguiensis would definitely expose to heavy metal have the ability to accumulate and biomagnified the contaminants. White shrimp which contaminated by heavy metal could cause danger if it is taken frequently and effect human health or can cause cancer. Methodology: The study was conducted in Kuala Selangor, Selangor. The study design of this study is cross-sectional study. Sampling data collection using Atomic absorption spectrum (AAS) for trace heavy metal in shrimp, modified Food Frequency Questionnaires (FFQ) and oral interview. A statistical analysis that is Microsoft Excel 2007 and statistical package for the social science (SPSS) version 17.0 was used in this study. Results: The study was found that Cd and Pb detection range of heavy metal concentration in wild shrimp (0.011 to 0.032 mg/kg, and 0.182 to 0.374 mg/kg) was slightly higher than aquaculture shrimp (0.000 to 0.022 mg/kg, and 0.066 to 0.294 mg/kg). While for Cu, the detection range of heavy metal concentration in aquaculture shrimp (0.751 to 1.416 mg/kg) was higher than wild shrimp (0.534 to 0.874 mg/kg). There was significantly different between wild shrimp and aquaculture shrimp (p < 0.001 ). Risk Assessment (RA) were calculating for both gender of consumer (male and female) and there was no hazard index value more than 1 (HI<1). Conclusion: In conclusion, Aquaculture shrimp was the main accumulation site for Cu while Cd and Pb were recorded higher in wild shrimp. This study revealed that Cd, Pb, and Cu concentrations in the shrimp were lower than the maximum permissible limit as recommended by the Malaysian Food Regulation 1985, Maximum Limit set by JECFA and FAO. After risk exposure were calculate, the result found that shrimp from Kuala Selangor area were deemed save for human consumption.